Going mobile: The effects of smartphone usage on internet consumption - Luis Aguiar (European Commission, Joint Research Centre (JRC), 2019)
With relatively small screens and limited display, smartphones significantly affect users' online browsing experience relative to fixed devices like the desktop. As consumers increasingly access the Internet through mobile devices, this paper explores the effects of a shift towards smartphone Internet access on the consumption of online content. Using data on the clickstream activity of over 2,900 individuals on both their smartphone and desktop, I estimate the effect of smartphone usage on users' allocation of time across various categories of websites, as well as their diversity and depth of online content consumption. Employing an instrumental variables approach based on updates of the smartphone operating system, the results show an increase in the usage of game and social networking domains at the expense of news and shopping domains - among others - as mobile usage increases relative to desktop. I also find that the diversity of consumption decreases within several categories, whereas consumption depth increases for games and social networking categories and decreases for search and news domains. Results show limited dif- ferences across consumer demographics. These results have important implications for website publishers, advertisers, and online competition.
Keywords: 330; Internet consumption; smartphones